SENI GRAFIS INDONESIA KEMBALI KE "JALAN MASIF" - Rahman, Deni (Brikolase : Jurnal Kajian Teori, Praktik dan Wacana Seni Budaya Rupa, 2017)
The graphic practitioners' tactics of exclusive graphics so that they are equal to painting, it makes graphic art seem only as one of the techniques of painting. To bring graphic art closer to society, taking a "massive ways" will be a powerful strategy. This will put the graphic arts back in their nature, namely multi-impression works.Â keywords: graphic art, massive